TRANSLATION TECHNIQUE OF ENGLISH ABSTRACT TRANSLATION IN JOURNAL EDUNOMIKA IN 2018 - Tira Nur Fitria (Elite : English and Literature Journal, 2018)
The objectives of the study are to identify the types of translation techniques and to find out the most dominant type of the translation techniques used in the translation of journal abstracts Edunomika STIE AAS Surakarta in Vol 2, No 01 (2018). The study used a descriptive qualitative design. Descriptive qualitative is a method of research that makes the description of the situation or events or occurrences clearer. It provides the description of situation or events or occurrences, so this method is an intention to accumulate the basic data. The data were taken from sixteen translation of journal abstracts Edunomika STIE AAS Surakarta in Vol 2, No 01 (2018). The finding shows that there were five translation techniques used in journal abstracts, they are Transposition/Shift (126 data or 75,90%), Reduction/Omission (21 data or 12,65%), Amplification/Addition (8 or 4,82%), Established Equivalence (6 or 3,61%) and Borrowing (5 data or 3,01%). The most dominant type of translation technique is Transposition/Shift. This technique replaces the grammatical categories of the source language (SL) into the target language (TL). This technique is usually used because of a different grammar between SL and TL. Transposition is the process where parts of the speech change their sequence when they are translated.